An Analysis of the TikTok Application as a Media Learning for English Learning - Ita Rosita; Nur Azmi Rohimajaya (Journal of English Education Studies, 2026)
TikTok is a social media platform that makes it possible users create short videos accompanied by various kinds a choice of features such as music, filter stickers and several other creative features. TikTok popularity allows many users, especially social groups young people, take advantage of this platform to obtain information and knowledge that is packaged concisely and clearly through TikTok content. Study This focuses on discussing the TikTok application for its users learn English through online video content shared by content creator on the popular hashtag #learntogether. This research using qualitative methods with an inductive approach. Finding research shows that TikTok can package language learning English interestingly. It was found that there are four types of subjects of application TikTok that are often made, namely vocabulary, grammar, pronunciation, and common mistakes. After research, it was concluded that there are more TikTok users like videos in the grammar category. Several factors TikTok has power attraction as a medium for learning English, namely short videos, delivery of material that is clear and not monotonous, coupled with effects features and writing and emojis can have a positive impact user learning process.